Black walnut as a valuable stand-forming tree species in Hungary – a growing technology review - Rédei, Károly; Antal, Borbála (Acta Agraria Debreceniensis, 2017)
In Hungary black walnut (Juglans nigra L.) is one of the most valuable exotic tree species, mainly because of its excessively liked wood for furniture industry, that has fine tissue and singular colour. Generally it is established by seeding, it can be regenerated by coopice shoot well, but not by seeding in natural way. Black walnut crops regurarly from the age of 25–30 years and its rotation age is 75–85 years. Prosperous decorative shape of stem allows its using in tree plantings out of forests, too. In the future its role can increase mainly on good.